PENINGKATAN KEMAMPUAN BERPIKIR LOGIS SISWA MELALUI PEMBELAJARAN MATEMATIKA REALISTIK - eva yanti siregar (Institut Pendidikan Tapanuli Selatan, 2018)
The current learning process tends to be memorized. Students should use thinking activities to rediscover knowledge but what happens is memorizing concepts in learning activities. The low ability of students to think mathematically, especially logical thinking, is often found in the analysis of learning outcomes. Logical thinking is the ability to use thinking power systematically to produce a correct conclusion. Optimizing students 'thinking activities through providing real-world problems that are close to students so that concepts as if rediscovered through Realistic Mathematics Education (RME) are an alternative in improving students' Logical Thinking Ability. This research is a study of the improvement of mathematical logical thinking ability of students' given RME. The study design used pretest posttest control group design. The study was carried out on students' of class VII Padangsidimpuan Middle School 6 which involved 2 sample classes namely class VII-1 as an experimental group and Class VII-2 as a control group. Data analysis used is N-gain test and T-Test Test. Through the tests carried out, it can be concluded that the increase of mathematical logical thinking ability students' who were given RME (N-Gain = 0.42) Furthermore, there was a significant difference in the improvement of mathematical logical thinking ability students who were given RME with mathematical logical thinking ability students' with ordinary learning.